Computational analysis study of aerodynamic vehicle passenger car (front grill) - Muhamad Khairul Hakimi , Hamid (2012)
Designing the front grill with the focus on an improvement aspect is very important in the automotive industry. This study proposes are to increase performance of the front grille and study effect of aerodynamic flow through the front grill using Computational Fluid Dynamic CFD. The difference speed which is at 80km/h, 120km/h and 180km/h was applied to obtain the flow structure around a passenger car with three design consideration of front grill. In this paper, the CFD simulation of Ansys FLUENT flow was applied to measure the result in the wind tunnel of passenger car design. The numerical method required to solve the Nervier–Stokes equations for incompressible and three-dimensional fluid motion. Result from three different discretization are compared with the past experiment data. In general, the characteristic of velocity and pressure counters was compared with three different speeds by symmetrical plane. Validation of drag and pressure effected on front grill also discussed to optimize the best aerodynamic flow of passenger car to all three design. Finally, the aerodynamics of the best design of front grill are introduced and analyzed.